N2-to-NH3 conversion by excess electrons trapped in point vacancies on 5f-element dioxide surfaces - Wang, Gaoxue; Batista, Enrique R.; Yang, Ping (Frontiers in Chemistry, 2023)
Ammonia (NH3) is one of the basic chemicals in artificial fertilizers and a promising carbon-free energy storage carrier. Its industrial synthesis is typically realized via the Haber−Bosch process using traditional iron-based catalysts. Developing advanced catalysts that can reduce the N2 activation barrier and make NH3 synthesis more efficient is a long-term goal in the field. Most heterogeneous catalysts for N2-to-NH3 conversion are multicomponent systems with singly dispersed metal clusters on supporting materials to activate N2 and H2 molecules. Herein, we report single-component heterogeneous catalysts based on 5f actinide dioxide surfaces (ThO2 and UO2) with oxygen vacancies for N2-to-NH3 conversion. The reaction cycle we propose is enabled by a dual-site mechanism, where N2 and H2 can be activated at different vacancy sites on the same surface; NH3 is subsequently formed by H− migration on the surface via associative pathways. Oxygen vacancies recover to their initial states after the release of two molecules of NH3, making it possible for the catalytic cycle to continue. Our work demonstrates the catalytic activities of oxygen vacancies on 5f actinide dioxide surfaces for N2 activation, which may inspire the search for highly efficient, single-component catalysts that are easy to synthesize and control for NH3 conversion.